THE EFFECT OF PROFESSIONAL RECOGNITION, EFFECT OF THE WORK ENVIRONMENT, SOCIAL VALUES, JOB MARKET CONSIDERATIONS, AND LOCUS OF CONTROL ON CAREER SELECTION OF PUBLIC ACCOUNTING: English - Tifania Sunaryo; Hasnawati (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2023)
This study aims to examine empirical evidence of the influence of the work environment, social values, labor market considerations, and personality on the career choices of accounting students as public accountants. This study uses primary data collected by using a questionnaire as an instrument of data collection techniques with final semester students as respondents who have taken the Audit 1 course majoring in accounting. The method used to determine the sample is purposive sampling with the number ofsamples used is 105 people. The data analysis technique used is multiple linear regression analysis. The results of the study indicate that social values affect career choice as a public accountant, while professional recognition, the influence of the work environment, social values, the influence of labor market considerations and locus of control do not affect the career choice of public accountants.